High-throughput wafer-level hydrogen sensor, method of manufacture and applications
Patent Information
- Application Number
- CN202611190171.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
但是,金属氧化物中的晶格氧往往是通过化学键与金属离子相连的,其稳定性往往较高,如何提升其晶格氧的活性,仍然不得其解
[0014]本方案实现气敏材料仅在预设敏感区生长,无边缘溢料、器件间串扰,单晶圆300颗以上器件电学、气敏响应离散度<5%;原位生长材料与衬底键合,对比浆料涂覆,附着力提升,经超声震动和高温长期老化无脱落,器件寿命不间断连续监测近2年无衰减。从而实现替代传统粉体浆料涂覆、溅射薄膜等传统工艺,图案精度达微米级,单晶圆可集成数百颗独立且性能稳定传感器,实现晶圆级高通量器件同步制备。
Smart Images

Figure CN123008906A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogen sensor technology, specifically relating to a high-throughput wafer-level hydrogen sensor, its preparation method, and its application. Background Technology
[0002] Traditional oxygen-adsorbed hydrogen sensors rely primarily on the active adsorption of oxygen (O2) on the surface of the gas-sensitive material for their gas-sensing response performance. C The concentration of ) therefore the sensor's response value is related to O C The concentration of oxygen is positively correlated with the concentration of oxygen. Therefore, a decrease in the partial pressure of oxygen in the environment will significantly affect the accuracy and stability of the sensor, and it may even fail to function properly in environments with low oxygen content. To date, most researchers tend to rely on O2 concentration... C The response mechanism model was used to design gas-sensitive materials in order to increase the surface activity of O. C The concentration of lattice oxygen in gas-sensitive materials is often overlooked because it is considered a stable oxygen species. However, lattice oxygen, which is abundant in these materials, is often assumed to exist stably within the material, thus neglecting its role in the gas-sensing reaction. In recent years, a few scholars have reported that under conditions of low oxygen partial pressure or even near-oxygen-free environments, some sensors still exhibit gas-sensing response values comparable to those under oxygen-rich conditions. This indirectly confirms that lattice oxygen in sensors may also participate in the gas-sensing reaction as active oxygen, thereby improving the sensor's gas-sensing performance and expanding its application range under different oxygen partial pressures. However, lattice oxygen in metal oxides is often linked to metal ions through chemical bonds, resulting in relatively high stability. How to improve the activity of this lattice oxygen remains a mystery.
[0003] Furthermore, traditional gas-sensitive materials often involve prioritizing the design and preparation of powder gas-sensitive materials, followed by coating them onto the chip surface as a slurry. This often results in weak adhesion between the material and the chip substrate, affecting the long-term stability of the sensor. Additionally, this approach can lead to agglomeration of the gas-sensitive material, impacting the sensor's sensitivity and device consistency.
[0004] Therefore, to address the aforementioned technical issues, it is necessary to provide a high-throughput wafer-level hydrogen sensor, its fabrication method, and its application. Summary of the Invention
[0005] The purpose of this invention is to provide a high-throughput wafer-level hydrogen sensor, its preparation method, and its application.
[0006] To achieve the above objectives, a specific embodiment of the present invention provides the following technical solution:
[0007] High-throughput wafer-level hydrogen sensor, including:
[0008] The chip body has a first region formed on its sensitive area for in-situ growth of gas-sensitive materials;
[0009] The gas-sensitive deposition structure consists of a gas-sensitive material layer with high lattice oxygen activity formed by the interface contact and deposition of a precursor reaction solution including a metal salt with the first region. A noble metal structure layer is also formed on the gas-sensitive material layer, wherein:
[0010] The concentration of metal salt in the precursor reaction solution is 0.1 mM-500 mM (based on metal atoms), the reaction temperature is 0-120℃, and the reaction time is 0.5-24 hours.
[0011] The metal ion M of a metal salt is at least one of the following: Sn 2+ Sn 4+ Ni 2+ In 3+ Ti 2+ Zn 2+ .
[0012] In one or more embodiments of the present invention, the precursor reaction solution comprises: metal ion M, 0.1 mM-500 mM; pH adjuster, 0.1 mM-500 mM; and deionized water as solvent.
[0013] pH adjusters are selected from one or two of the following reagents: urea, ammonia, ammonium chloride, ammonium fluoride, sodium hydroxide, potassium hydroxide, citric acid / citric acid salt, and Triton.
[0014] This solution enables the growth of gas-sensitive materials exclusively within a pre-defined sensitive area, eliminating edge overflow and crosstalk between devices. For over 300 devices per wafer, the electrical and gas-sensitive response dispersion is less than 5%. In-situ growth and substrate bonding significantly improve adhesion compared to paste coating. The materials show no detachment after long-term ultrasonic vibration and high-temperature aging, and device lifespan remains unchanged after nearly two years of continuous monitoring. This solution replaces traditional processes such as powder paste coating and sputtering thin films, achieving micron-level pattern precision. Hundreds of independent and stable sensors can be integrated onto a single wafer, enabling simultaneous fabrication of high-throughput wafer-level devices.
[0015] Furthermore, this scheme employs control of the precursor reaction solution at lower temperatures and shorter reaction times. Low-temperature, short-time growth inhibits grain growth and reduces oxygen vacancies in the material. The proportion of lattice oxygen () has increased significantly. The activation level was significantly improved; samples grown for 2-3 hours showed increased O L Samples with a content lower than 5h showed a significantly higher response to 500 ppm hydrogen than 5h samples with higher crystallinity. Furthermore, samples grown for 2h showed a significant difference in O2 content before and after contact with hydrogen under the same operating conditions. L The content decreased from 17.58% to 8.43%, and a significant increase in the content of low-valence states of metal elements was also detected in the entire composite material system during this process, all of which prove that this low-crystallinity sample has higher O content.L It exhibits high reactivity and a higher response value to hydrogen; liquid-phase self-assembly forms a porous nanostructure, theoretically with a higher specific surface area than planar gas-sensitive material films obtained by sputtering, increasing the number of hydrogen adsorption sites, achieving an average response value of 40223.6 for 500ppm H2, and providing a wide hydrogen detection range (0.05 - 50000 ppm); lattice oxygen participates in the gas-sensing reaction, eliminating the need for traditional sensors that rely solely on surface-adsorbed oxygen. Despite limitations, it can still function normally even when the oxygen concentration is as low as 2%.
[0016] In one or more embodiments of the present invention, the noble metal structural layer is obtained by modifying with a first noble metal and then annealing. The first noble metal is selected from at least one of the following: gold, silver, platinum, palladium, ruthenium, rhodium, osmium, and iridium. The noble metal catalyst used in this scheme catalyzes the dissociation of H2 molecules, reduces the activation energy of the hydrogen oxidation reaction, and lowers the sensor operating temperature by 20-200°C. The noble metal forms a Schottky junction with the metal oxide, regulating carrier migration. The catalytic overflow effect of the noble metal combined with the high lattice oxygen reactivity of the metal oxide allows the hydrogen detection limit to reach 0.05 ppm.
[0017] In one or more embodiments of the present invention, annealing includes at least one of the following steps: first annealing and second annealing; wherein the conditions for first annealing are: 100-600℃, first atmosphere, 1-5h; and the conditions for second annealing are: annealing temperature slightly higher than the sensor's operating temperature, oxidizing atmosphere, 20-300h. In this scheme, high-temperature inert annealing in the first annealing process breaks weakly bonded lattice oxygen, creating a large number of oxygen vacancies and maximizing lattice oxygen activity; low-temperature oxidizing annealing in the second annealing process moderately replenishes lattice oxygen, eliminating unstable defects generated by annealing. After 300h continuous aging under operating conditions, the device shows no performance degradation for nearly two years; the two-stage annealing eliminates residual organic matter and chloride ion impurities from liquid phase growth, resulting in uniform material conductivity and significantly improved consistency of the wafer array device.
[0018] In one or more embodiments of the present invention, the first atmosphere is an inert gas atmosphere or a reducing gas atmosphere, wherein the inert gas is selected from at least one of argon and nitrogen, and the reducing gas is selected from at least one of hydrogen and methane, or a mixture of at least one of these with the inert gas. Preferably, when the reducing gas and the inert gas are mixed, the reducing gas content is 0-100V / V.
[0019] In one or more embodiments of the present invention, the oxidizing atmosphere is an atmosphere containing 0.5-100V / V% oxygen in nitrogen or air.
[0020] In one or more embodiments of the present invention, a method for fabricating a high-throughput wafer-level hydrogen sensor includes: S1, preparing a chip substrate; S2, according to the sensor design requirements of the chip substrate, using micro-nano fabrication technology, exposing a first region of the designed sensor with a mask, the first region being used for in-situ growth of a patterned gas-sensitive material layer; S3, placing the exposed chip substrate in a precursor reaction solution to complete the in-situ patterned growth of a metal oxide-based gas-sensitive material to form a gas-sensitive material layer; S4, removing the mask, modifying the surface of the gas-sensitive material layer with a noble metal to form a noble metal structure layer, and annealing to obtain a wafer-level hydrogen sensor.
[0021] In one or more embodiments of the present invention, in step S1, the chip substrate is formed by spin-coating photoresist on a substrate material, forming a photolithographic pattern on the substrate material by at least exposure, development and removal of residual photoresist, and then preparing an electrode array to obtain the chip substrate.
[0022] In one or more embodiments of the present invention, the substrate material is any one of silicon, silicon containing silicon dioxide, silicon nitride, gallium nitride, metal oxide ceramic, and polyimide.
[0023] In one or more embodiments of the present invention, the aforementioned high-throughput wafer-level hydrogen sensor is applied in multi-component gas sensing.
[0024] Compared with existing technologies, the high-throughput wafer-level hydrogen sensor, its fabrication method, and its application of the present invention can greatly improve the high throughput and consistency of the sensor through an in-situ patterned growth scheme, which is more conducive to the mass production of gas-sensitive sensors. Furthermore, due to its high lattice oxygen activity, it has higher sensitivity and a wider range of applications, and its dependence on oxygen partial pressure is lower than that of traditional hydrogen sensors. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a schematic diagram of the fabrication process of a wafer-level hydrogen sensor in one embodiment of the present invention;
[0027] Figure 2 This is a schematic diagram of the chip wafer structure in Embodiment 1 of the present invention, wherein 1 is the chip body and 2 is the electrode;
[0028] Figure 3Optical photographs of the chip in Embodiment 1 of the present invention before and after ultrasonic cleaning: (ac) optical photograph of the chip before cleaning, (df) optical photograph of the chip after ultrasonic cleaning.
[0029] Figure 4 This is a graph showing the response data of the sensor to 50 ppm hydrogen gas for 20 weeks in Embodiment 1 of the present invention;
[0030] Figure 5 An optical photograph of the sensor prepared using SnO2 / Pt powder material in Example 1 of this invention;
[0031] Figure 6 This is an optical photograph of the sensor prepared by the conventional method of coating gas-sensitive material slurry in Example 1 of the present invention;
[0032] Figure 7 This is a schematic diagram illustrating the effect of growth time on the crystallinity state of the material in Embodiment 2 of the present invention;
[0033] Figure 8 The graph shows the changes in the valence ratio of each element in the gas-sensitive material prepared in Example 2 of the present invention before and after contact with hydrogen under working conditions.
[0034] Figure 9 The diagram shows the gas sensing performance consistency (a) and electrical consistency (b) of the wafer-level hydrogen sensor in Embodiment 2 of the present invention.
[0035] Figure 10 This is a comparison chart of the response values of sensors prepared under different conditions in Example 2 of the present invention to 500 ppm hydrogen at different temperatures;
[0036] Figure 11 The following are the dynamic response curves of the sensors prepared under different growth time conditions in Example 2 of the present invention to different concentrations of hydrogen gas ranging from 0.05 to 20000 ppm: (a) 0.05-10 ppm, (b) 10-20000 ppm;
[0037] Figure 12 This shows the changes in the sensor's response to 20 ppm and 500 ppm hydrogen over 20 months in Embodiment 2 of the present invention.
[0038] Figure 13 SEM images of discontinuous materials grown in low-concentration SnCl2 salt solution;
[0039] Figure 14 SEM images of materials grown in 3 mM SnCl2 and 4 mM ammonium fluoride solutions after annealing;
[0040] Figure 15SEM image of gas-sensitive material grown in a high-concentration 300mM SnCl2 solution;
[0041] Figure 16 A graph showing the cyclic test of a sensor without a second aging process against 500 ppm hydrogen.
[0042] Figure 17 The sensor's response to 10 ppm and 50 ppm hydrogen without high-temperature annealing in an inert or reducing atmosphere. Detailed Implementation
[0043] To enable those skilled in the art to better understand the technical solutions in this disclosure, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments disclosed herein. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments in this disclosure, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this disclosure.
[0044] Driven by the need for adsorbed oxygen-type hydrogen sensors, the in-situ design and fabrication of patterned gas-sensitive materials with high lattice oxygen activity for the preparation of high-throughput hydrogen sensors has become a major research hotspot. While existing sputtering methods can also achieve patterned fabrication of gas-sensitive materials, these methods often result in thin-film gas-sensitive materials with relatively low specific surface area and high cost, and cannot systematically control the crystallinity and lattice oxygen activity of the gas-sensitive material. To address these issues, it is necessary to provide methods for preparing gas-sensitive materials with high lattice defects, reducing the crystallinity of the material to improve lattice oxygen activity, and ultimately enhancing the gas-sensing performance of the sensor.
[0045] The purpose of this invention is to provide an in-situ design and control method for highly active lattice oxygen-sensitive materials, used to prepare high-stability, high-throughput hydrogen sensors and broaden their application scenarios. Furthermore, due to the high lattice oxygen activity of the sensor, it exhibits higher sensitivity and a wider range of applications, with lower dependence on oxygen partial pressure compared to traditional hydrogen sensors.
[0046] To achieve the above objectives, an embodiment of the present invention provides the following technical solution: a method for fabricating a high-throughput wafer-level hydrogen sensor, comprising:
[0047] S1. Prepare the chip substrate;
[0048] S2. Based on the sensor design requirements of the chip substrate, micro-nano fabrication technology is used to expose the first region of the designed sensor with a mask template. The first region is used to grow a patterned gas-sensitive material layer in situ.
[0049] S3. Place the exposed chip substrate in the precursor reaction solution to complete the in-situ patterned growth of the metal oxide-based gas-sensitive material to form a gas-sensitive material layer.
[0050] S4. Remove the mask template, modify the surface of the gas-sensitive material layer with noble metal to form a noble metal structure layer, and anneal to obtain a wafer-level hydrogen sensor.
[0051] Specifically, it may include the following steps:
[0052] S1. Select a suitable substrate material according to the application scenario and design requirements, and use micro-nano fabrication technology to prepare a chip substrate through a series of techniques such as exposure, development and coating, for in-situ growth of gas-sensitive materials.
[0053] S2. Based on the structure and design requirements of the chip substrate, micro-nano processing technology is used, such as using patterned photoresist as a mask to expose the sensitive area (i.e., the first region) of the sensor for in-situ growth of patterned gas-sensitive materials.
[0054] S3. Place the chip substrate with the exposed sensitive area in the precursor reaction solution of the metal salt solution to complete the in-situ patterned growth of the metal oxide-based gas-sensitive material, thereby forming a gas-sensitive material layer with high lattice oxygen activity.
[0055] S4. After removing the photoresist, further modify the material surface with metals such as gold, silver, platinum, palladium, ruthenium, rhodium, osmium, iridium, etc. These can be single-metal catalysts, bimetallic catalysts, or trimetallic catalysts. After the first annealing at 100-600℃ in an inert atmosphere (or reducing atmosphere), a second annealing is performed in an oxidizing atmosphere to obtain a wafer-level hydrogen sensor.
[0056] Furthermore, in step S1, the chip structure design of the substrate material can be designed as a chip without heating electrodes, or it can be designed as a micro hot plate chip with integrated heating electrodes according to the gas-sensitive properties of the material.
[0057] Furthermore, in step S2, the pattern of the photoresist mask can also be adjusted according to the chip structure of the sensor.
[0058] Furthermore, in step S3, in order to ensure the consistency of the hydrogen sensor on the wafer-level substrate material and avoid differences in the amount of solute contained in different precursor reaction solutions, the entire wafer is inverted at a fixed depth during the material growth process to ensure that the first region exposed by the entire wafer-level substrate material is used for in-situ patterned growth of the gas-sensitive material under the same conditions.
[0059] Furthermore, in step S3, the solute in the precursor reaction solution of the metal oxide-based gas-sensitive material is Sn. 2+ Sn4+ Ni 2+ In 3+ Ti 2+ Zn 2+ One or more water-soluble metal salts are used, and according to the reaction characteristics of different metal salts, some reagents are added during the in-situ growth process to regulate the pH of the precursor reaction solution and to add complexing agents to promote material growth. The concentration of the above reaction salt solution is 0.1mM-500mM.
[0060] Furthermore, in order to improve the lattice oxygen activity of the gas-sensitive material, based on the material's reaction characteristics, a lower growth temperature and a shorter growth time are selected as much as possible while ensuring the material can grow normally, so as to reduce the crystallinity of the metal oxide material. This limits the reaction temperature for in-situ patterned growth of the gas-sensitive material to 0-120℃ and the reaction time to 0.5-24 hours.
[0061] Furthermore, in step S4, to avoid some residual photoresist adsorbing onto the surface of the gas-sensitive material during the removal process, the entire wafer-level substrate material after growth must be inverted and immersed in a second solution such as acetone or N-methylpyrrolidone for 1-5 hours (the appropriate second solution is selected according to the properties of the photoresist, which is common knowledge for those skilled in the art and will not be elaborated here). During the photoresist removal process, the solution can be replaced 1-2 times to completely remove the photoresist.
[0062] Furthermore, in step S4, the in-situ modification method of the noble metal catalyst can be achieved by inverting the chip in a noble metal solution and slowly adding a reducing agent (such as ascorbic acid, sodium borohydride, etc.) for in-situ reduction, or by photo-assisted heating reduction. Alternatively, it can be achieved directly by vapor deposition, controlling the vapor deposition time and power of the metal source to in-situ modify metal nanoparticles with high hydrogen catalytic activity.
[0063] Furthermore, to further enhance the lattice oxygen activity of the sensor's gas-sensitive material, in step S4, the hydrogen sensor modified with noble metal nanoparticles is first annealed at a relatively high temperature (100-600℃) in an inert (or reducing) atmosphere to further pyrolyze the unstable lattice oxygen bonds in the metal oxide. Moreover, to ensure the high stability of the sensor with high lattice oxygen activity, the annealed sensor is further annealed and aged (20-300h) in an oxidizing atmosphere at a temperature slightly higher than the sensor's operating temperature (which can be 30-100℃), such as 50-350℃. This replenishes some of the pyrolyzed lattice oxygen while ensuring excellent material stability of the sensor under normal operating conditions.
[0064] The present invention also provides an application of the aforementioned hydrogen sensor in the sensing of multi-component gases.
[0065] In one embodiment: such as Figure 1 As shown, the fabrication process of the wafer-level high lattice oxygen activity hydrogen sensor of the present invention can be as follows:
[0066] S1. Obtain a chip wafer with a metal electrode array fabricated on it. Figure 1 (a)
[0067] S2. A chip wafer containing a photoresist mask is obtained through micro-nano fabrication, and the sensitive area for material growth is exposed, which is then used as a substrate for the growth of metal oxide-based gas-sensitive materials. Figure 1 (b)
[0068] S3. Adjust the proportions of each reagent in the precursor during the growth of the gas-sensitive material, and regulate the temperature and time of material growth to obtain a metal oxide material with high lattice oxygen activity and high gas-sensing performance. Figure 1 (c)
[0069] S4. After removing the photoresist mask from the surface, a noble metal material with high catalytic activity for hydrogen is modified in situ, and then a series of annealing processes are performed to obtain a high-throughput, high-stability wafer-level hydrogen sensor. Figure 1 (d).
[0070] Specifically:
[0071] In step S1, photoresist is spin-coated onto the substrate material, and the designed photolithographic pattern is formed on the substrate by exposure, development and removal of residual photoresist in sequence. Then, a metal electrode array is prepared by evaporation or magnetron sputtering to obtain a chip wafer.
[0072] The substrate material is primarily any one of silicon, silicon containing silicon dioxide, silicon nitride, gallium nitride, metal oxide ceramics, or polyimide (PI). The metal electrode material is any one or more of gold (Au), silver (Ag), platinum (Pt), molybdenum (Mo), titanium (Ti), and chromium (Cr).
[0073] In step S2, photoresist is spin-coated again on the chip wafer. A photoresist mask is formed on the chip substrate by exposure, development and removal of residual photoresist, exposing the gas-sensitive material growth area, i.e., the first exposed area.
[0074] Among them, the photoresist materials are mainly commonly used photoresist models such as AZ4620, AZ5214, SU-8 series, RZJ-390 series, RFJ-210 series, NR series, etc.
[0075] In step S3, the solute concentration of the metal salt solution used for the self-assembly growth of the gas-sensitive material is 0.1 mM-500 mM, the concentration of the reagent additives (such as Triton, ethanolamine, urea, ammonium chloride, ammonium fluoride, etc.) is 0.1 mM-500 mM, and the growth temperature is 0-120℃. The gas-sensitive material in the gas-sensitive material layer is any one or a combination of multiple composite nanomaterials formed from oxides of metal ions.
[0076] In step S3, to achieve in-situ uniform growth of the gas-sensitive material, the chip wafer is inverted and placed at a fixed depth in the solution during the growth process. This prevents poor uniformity caused by uneven solute distribution at different depths. This depth can be determined by the support pillars in the designed container. When inverting the wafer, to maximize the use of all wafer area, the wafer is fixed to the fixing plate with double-sided adhesive. However, when the growth temperature is higher than 100°C, a suitable container is selected, and the wafer is directly placed on the support pillars in the container. The fixing plate and support pillars can be made of polytetrafluoroethylene, glass, ceramics, etc. The entire wafer is immersed in the precursor solution at the same depth, avoiding the solute concentration gradient in the vertical direction of the solution; the wafer grows with its face down, impurities and bubbles float away from the sensitive area, and the surface defect density of the material is reduced by 60%; hundreds or even thousands of devices (depending on the size of the chip design) can be grown simultaneously on a single wafer, significantly reducing the manufacturing cost of a single sensor.
[0077] In step S4, to prevent residual photoresist from adsorbing onto the surface of the gas-sensitive material during the photoresist removal process, the entire wafer must be inverted and immersed in a photoresist removal solution such as acetone or N-methylpyrrolidone for 1-5 hours (the appropriate solution, immersion time, and temperature should be selected based on the properties of the photoresist). The solution can be replaced 1-2 times during the removal process. The final result is a chip wafer containing in-situ patterned growth (e.g., ...). Figure 1 (as shown in d).
[0078] In step S4, the modified precious metals include single precious metals such as gold, silver, platinum, palladium, ruthenium, rhodium, osmium, and iridium, or bimetallic and ternary metals.
[0079] In step S4, the in-situ modification of precious metals can be achieved by metal vapor deposition, liquid phase reducing agent reduction, or liquid phase photothermal reduction.
[0080] In step S4, based on the control of the metal oxide material growth conditions in step S3, the wafer after in-situ modification with noble metal is further modified by controlling the subsequent annealing conditions to obtain a hydrogen sensor with high lattice oxygen activity and high stability under operating conditions. Specifically, it is first annealed for 1-5 hours in an inert atmosphere or reducing atmosphere (such as pure argon, pure nitrogen, argon or nitrogen containing different concentrations of hydrogen (0-100v / v%) or methane gas (0-100v / v%), etc.). The temperature of this annealing stage is relatively high (100-600℃; it should be noted that the specific temperature limit here can be selected according to different materials, and since the chip wafers are placed in the center of the annealing furnace, and the temperature distribution of the furnace in this area is relatively uniform, the temperature difference of each chip on the entire wafer is small, which is conducive to obtaining the overall stability of the wafer annealing) to thermally decompose and connect the less stable lattice oxygen. The wafer is placed in the center of the annealing furnace to maintain the uniformity of heating throughout the wafer. Then, under an oxidizing atmosphere (oxygen content in nitrogen (2-100%)), the hydrogen sensor is annealed and aged at a temperature slightly higher than that of the sensor for 20-300 hours to replenish some of the lattice oxygen lost through pyrolysis. The annealing temperature range at this time is (100-350℃), which combines the stability of the sensor with high lattice oxygen activity, thus completing the fabrication of a wafer-level high-stability and high-performance hydrogen sensor.
[0081] The principle of this invention for fabricating a high-performance hydrogen sensor at the wafer level based on high lattice oxygen activity is as follows: by utilizing the influence of growth time and growth temperature on the morphology, thickness and crystallinity of the gas-sensitive material, combined with the control scheme of the annealing process, a gas-sensitive material with high lattice oxygen activity can be obtained while also exhibiting excellent stability under operating conditions.
[0082] The present invention will be further described below with reference to specific embodiments.
[0083] Example 1: Wafer-level SnO x Fabrication of a high-performance Pt hydrogen sensor.
[0084] 1. Arrayed metal electrodes are fabricated on a substrate using micromachining technology. In this embodiment, a wafer-level single-crystal silicon wafer substrate is used.
[0085] Customized photolithography patterns are used to fabricate metal electrode arrays on a substrate through multi-step photolithography, development, and coating techniques. Figure 2 As shown. Figure 2 The image shows a pattern of a conventional interdigitated electrode fabricated on a silicon oxide substrate.
[0086] 2. A porous material mask template made of AZ4620 photoresist is prepared on a wafer using micromachining to expose the interdigitated electrode region of the electrode chip for subsequent patterned in-situ growth of gas-sensitive materials.
[0087] 3. In-situ patterned growth of SnO2.
[0088] The substrate was placed upside down in a deionized aqueous solution containing 3 mM SnCl2 and 4 mM urea, with a solution depth of 4 cm and a chip height 1 cm above the bottom of the container. The oven temperature was set to 95°C (at this temperature, although decomposition during growth will produce a certain amount of ammonia and CO2, the former can participate in complexation as ammonium ions, and the latter can adjust the pH value to a certain extent to balance the reaction environment), and the reaction time was 8 hours. After the reaction, the chip was removed from the solution and rinsed with clean water. Then, a suitable container was selected, and the chip was placed upside down or tilted face down in an acetone solution for 2 hours. The chip was then removed and rinsed sequentially with acetone, ethanol, and water, with the same face down, and finally dried with nitrogen.
[0089] 4. Modification of Pt nanoparticles
[0090] The chip was immersed in a 5 mM chloroplatinic acid solution for 20 minutes, and then removed and placed at a 365 nm power of 50 mW / cm². 2 Irradiate under ultraviolet light for 15 minutes, then rinse thoroughly with water and dry with nitrogen.
[0091] 5. After completing the in-situ growth and assembly of the gas-sensitive material, anneal it at 500℃ for 2 hours in a nitrogen atmosphere, and then age it at 250℃ for 36 hours in an air atmosphere.
[0092] In this embodiment, the material grown in situ using patterned growth exhibits strong adhesion to the substrate. After ultrasonication at 30 W for 5 minutes, no material detachment was observed in any of the multiple devices. Figure 3 As shown. Figure 3 ac is an optical photograph of the device after in-situ patterned material growth. Figure 3 Image df is an optical photograph of the device after ultrasonic cleaning. Continuous monitoring of the sensor's response to 50 ppm hydrogen at an operating temperature of 200°C showed that, due to the high bonding strength between the material and the substrate, the sensor's response value changed by approximately 11% (standard deviation 0.8) over 20 weeks, demonstrating its excellent stability. Figure 4 As shown; compared with the traditional method of dripping or coating gas-sensitive material slurry on the chip surface, the gas-sensitive material grown in situ with patterning exhibits higher material uniformity and better adhesion. Figure 5Optical images of a SnO2 / Pt-based hydrogen sensor fabricated by drop-coating show uneven material distribution on the chip surface. Some chips exhibited material detachment during annealing due to thermal stress mismatch between the material and the chip substrate. Segmented annealing conditions reduced the sensor's dependence on oxygen partial pressure. Figure 6 As shown, the sensor can still work normally when the oxygen concentration is only 2%, and its response value is slightly higher than that under normal air conditions (21% oxygen), which fully proves that the lattice oxygen of the sensor participates in the reaction.
[0093] Example 2: Wafer-level SnO x Fabrication of a high-performance Pd hydrogen sensor.
[0094] 1. This embodiment uses a silicon-based chip containing 300 nm silicon oxide as a substrate to fabricate a wafer-level micro hotplate chip array. The steps are similar to those in Embodiment 1, involving the deposition or sputtering of electrodes on the substrate surface. However, each micro hotplate chip has two pairs of electrodes: interdigitated test electrodes and heating wire electrodes (heating electrodes) deposited or sputtered from a Pt target. The test electrodes are used to detect changes in the electrical properties of the gas-sensitive material before and after the sensor comes into contact with hydrogen gas at a given bias voltage (1-10V). The heating electrodes provide the chip with an operating temperature at a given bias voltage (0.5-10V). The heating principle is that when a voltage is applied to the heating electrodes, Joule heating is generated on the Pt heating wire, thus providing a specific operating temperature for the sensor chip. The generated Joule heating is related to the voltage applied to the heating electrodes. The size and shape of the micro hotplate are those commonly used by those skilled in the art.
[0095] 2. A porous material mask template made of AZ4620 photoresist is prepared on a wafer using micromachining to expose the interdigitated electrode region of the electrode chip for subsequent patterned in-situ growth of gas-sensitive materials.
[0096] Step 2 of this embodiment is basically the same as step 1 of the embodiment, except that the chip substrate has been changed, thereby redesigning the chip mask pattern and the subsequent photoresist mask pattern.
[0097] 3. SnO x In situ growth.
[0098] The chip substrate was placed upside down in a solution containing 3 mM SnCl2 and 4 mM urea, with the height of the chip relative to the bottom of the container set to 1 cm. The oven temperature was set to 90℃, and the reaction time was 2-5 hours. After the reaction, the chip was removed from the solution and rinsed with clean water. Then, a suitable container was selected, and the chip was placed upside down or tilted face down in an acetone solution for 2 hours. The chip was then removed, rinsed face down with acetone, ethanol, and water, and finally dried with nitrogen gas. Figure 7 The results show the effect of different growth times on the crystallinity of the material. As the growth time increases, the lattice oxygen content of the material gradually increases, proving that its crystallinity is higher.
[0099] 4. Modification of Pd nanoparticles
[0100] Pd nanoparticles were used to modify SnO in situ using electron beam evaporation. x The surface of the material was modified with Pd nanoparticles by setting the evaporation rate to 0.15 Å per second and the time to 5 seconds.
[0101] 5. After completing the in-situ growth and noble metal modification of the gas-sensitive material, it is annealed at 400℃ for 2 hours in an argon atmosphere, and then aged at 200℃ for 36 hours in an air atmosphere. Figure 7 The prepared SnO x The changes in the proportions of X-ray photoelectron spectroscopy of each element in the Pd gas-sensitive material before and after contact with hydrogen under operating conditions. In a hydrogen-containing atmosphere, the lattice oxygen content in the composite material is significantly reduced (…). Figure 8 a), and Sn ( Figure 8 b) and Pd ( Figure 8 The increase in low-valence elements in c) proves that the material prepared in this embodiment is a hydrogen gas-sensitive material with high lattice oxygen activity.
[0102] 6. After the wafer-level hydrogen sensor was fabricated, the response of over 300 sensors on the wafer to 500 ppm hydrogen gas was randomly tested. For example... Figure 9 As shown in Figure a, all sensors exhibited excellent gas-sensing response performance, and their response values were basically on the same order of magnitude. The differences between the baseline current value and the current value at which the steady-state response was achieved for all tested sensors were also relatively small. Figure 9 (b) This demonstrates that the sensors prepared using this method have very high consistency.
[0103] Sample detection in this embodiment is as follows: Figure 7-12 As shown, the growth time affects the regulation of lattice oxygen as follows: Figure 7 As shown:
[0104] 2-hour short-time growth: low crystallinity. =61.60% =20.97%, =17.43%, sufficient oxygen vacancies, optimal lattice oxygen activity; 3h medium growth: crystallinity slightly increased, lattice oxygen activity slightly decreased; 5h long growth: grains coarse. The proportion surged to 49.20%, but oxygen vacancies... With only 16.62%, the lattice oxygen bonds are strong, resulting in a significant decrease in activity, and the response value to 500 ppm hydrogen gas drops by two orders of magnitude. Figure 10 The catalytic effect of precious metal Pd: The optimal operating temperature of the unmodified sample was 350℃, and the response value to 500 ppm hydrogen was only 39.5. After Pd modification, the optimal operating temperature of the sensor was 150℃, which was reduced by 200℃, and its response to 500 ppm hydrogen was improved by two orders of magnitude. Figure 10 The sensor's detection limit is as low as 0.05 ppm. Figure 11 The sensor's response to 20 ppm and 500 ppm hydrogen showed no performance degradation over a period of 20 months (nearly two years). Figure 12 It exhibits excellent long-term stability; array consistency is as follows: Figure 9 As shown, the response curves of 300+ devices highly overlap, and the baseline current and steady-state current show no significant deviation, allowing for direct batch packaging without the need for individual screening.
[0105] Experimental Group 1
[0106] The only difference between Example 11 and Example 1 is that the powder material was obtained by growing SnCl2 3mM solution at 80℃ for 3h.
[0107] The only difference between Example 12 and Example 1 is that: the SnOx thin film was sputtered by magnetron sputtering on a silicon substrate with 300 nm silicon oxide;
[0108] The only difference between Example 13 and Example 1 is that: SnCl2 3mM, 80℃ / 3h, inverted growth, silicon substrate containing 300 nm silicon oxide, and no photoresist mask.
[0109] The only difference between Comparative Example 11 and Example 1 is that the SnO formulation is the same. x Powder slurry, dot-coated interdigitated electrodes, without in-situ patterning;
[0110] The only difference between Comparative Example 12 and Example 1 is that: magnetron sputtering of SnO x Thin-film, liquid-phase-free low-temperature oxygen vacancy generation process;
[0111] The only difference between Comparative Example 13 and Example 1 is that no photoresist mask is used, and gas-sensitive materials are grown uniformly on the entire wafer.
[0112] Comparison indicators: The sensor material prepared from powder slurry has poor adhesion to the substrate surface, poor uniformity of the slurry film, and poor performance consistency of the sensor. Figure 6 As shown); magnetron sputtering of metal oxides often requires high temperatures, resulting in high crystallinity of the particulate material and low utilization of lattice oxygen; indiscriminate in-situ growth of gas-sensitive materials can cause the electrode pattern of the chip to be covered by the material, making it impossible to encapsulate the chip through subsequent bonding and lead bonding.
[0113] Experimental Group 2
[0114] The only difference between Example 21 and Example 1 is that: low concentration of 0.5mM SnCl2, 4 mM urea, growth at 90℃ / 8h;
[0115] The only difference between Example 22 and Example 1 is that the concentration of SnCl2 is 3mM, the growth temperature is 90℃ / 8h, no urea is added, and only 4mM ammonium fluoride is added.
[0116] The only difference between Example 23 and Example 1 is that: high concentration of 300mM SnCl2, 4mM urea, and growth at 90℃ / 8h.
[0117] The only difference between Comparative Example 21 and Example 1 is that 0.5 mM SnCl2 cannot form a continuous gas-sensitive layer. Figure 13 As shown;
[0118] The only difference between Comparative Example 22 and Example 1 is that: without urea to regulate the pH of SnCl2 and the kinetics of the hydrolysis reaction, the growth rate of SnO2 was too fast, resulting in excessively high thermal stress between the material and the substrate. This caused the grown SnO2 nanosheet array film to crack and detach during the annealing process. Figure 14 As shown;
[0119] The only difference between Comparative Example 23 and Example 1 is that the concentration of the metal salt is too high, which promotes other reaction pathways during the reaction process. This results in the formation of layered SnO2 materials with low specific surface area during material growth, thus affecting the sensor's performance. Figure 15 As shown.
[0120] Experimental Group 3
[0121] The only difference between Example 31 and Example 1 is that only the first annealing is used, and the parameters are adjusted to N2500℃ / 2h;
[0122] The only difference between Example 32 and Example 1 is that only the second atmosphere annealing is used, and the air temperature is 500°C / 2h + air temperature is 200°C / 36h.
[0123] The only difference between Comparative Example 31 and Example 1 is that: only one inert annealing was performed, with no air aging, and the device experienced severe short-term drift. Figure 16 As shown;
[0124] The only difference between Comparative Example 32 and Example 1 is that: only high-temperature air annealing was performed, without pre-reduction, resulting in low lattice oxygen activity and low sensor sensitivity. Figure 17 As shown.
[0125] In summary, the hydrogen sensor fabrication method of this invention uses photoresist as a template to grow metal oxide-based gas-sensitive materials in situ. First, the crystallinity of the material is initially controlled by adjusting the growth temperature, time, and solution ratio. Then, after modifying the noble metal catalyst, a series of annealing processes are designed to ensure both high lattice oxygen catalytic activity and excellent stability under operating conditions. This method allows for low-cost, in-situ patterning of high-lattice oxygen-active gas-sensitive materials, increasing the bonding force between the material and the substrate, improving the stability and consistency of the sensor, expanding the sensor's application scenarios, and reducing the sensor's dependence on oxygen partial pressure to a certain extent.
[0126] It will be apparent to those skilled in the art that this disclosure is not limited to the details of the exemplary embodiments described above, and that this disclosure can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of this disclosure is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within this disclosure. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0127] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A high-throughput wafer-level hydrogen sensor, comprising: The chip body has a first region formed on its sensitive area for in-situ growth of gas-sensitive materials; A gas-sensitive deposition structure is formed by the interfacial contact and deposition of a precursor reaction solution including a metal salt with a first region to form a gas-sensitive material layer with high lattice oxygen activity. A noble metal structure layer is also formed on the gas-sensitive material layer, wherein: The concentration of the metal salt in the precursor reaction solution is 0.1 mM-500 mM (based on metal atoms), the reaction temperature is 0-120℃, and the reaction time is 0.5-24 hours. The metal ion M of the metal salt is at least one of the following: Sn 2+ Sn 4+ Ni 2+ In 3+ Ti 2+ Zn 2+ .
2. The high-throughput wafer-level hydrogen sensor according to claim 1, characterized in that, The precursor reaction solution comprises: metal ions M, 0.1 mM-500 mM; pH adjuster, 0.1 mM-500 mM; and deionized water as solvent. The pH adjuster is selected from one or two of the following reagents: urea, ammonia, ammonium chloride, ammonium fluoride, sodium hydroxide, potassium hydroxide, citric acid / citric acid salt, and Triton.
3. The high-throughput wafer-level hydrogen sensor according to claim 1, characterized in that, The precious metal structural layer is obtained by modifying with a first precious metal and then annealing it. The first precious metal is selected from at least one of the following: gold, silver, platinum, palladium, ruthenium, rhodium, osmium, and iridium.
4. The high-throughput wafer-level hydrogen sensor according to claim 3, characterized in that, The annealing process includes at least one of the following steps: first annealing and second annealing; wherein The conditions for the first annealing are: 100-600℃, first atmosphere, 1-5h; The conditions for the second annealing are: annealing temperature slightly higher than the sensor's operating temperature, oxidizing atmosphere, 20-300 hours.
5. The high-throughput wafer-level hydrogen sensor according to claim 4, characterized in that, The first atmosphere is an inert gas atmosphere or a reducing gas atmosphere, wherein the inert gas is selected from at least one of argon and nitrogen, and the reducing gas is selected from at least one of hydrogen and methane, or a mixture of at least one of them and the inert gas.
6. The high-throughput wafer-level hydrogen sensor according to claim 5, characterized in that, The oxidizing atmosphere is a nitrogen atmosphere containing 0.5-100V / V% oxygen or air.
7. The method for fabricating a high-throughput wafer-level hydrogen sensor according to any one of claims 1-6, comprising: S1. Prepare the chip substrate; S2. Based on the sensor design requirements of the chip substrate, micro-nano fabrication technology is used to expose the first region of the designed sensor with a mask template. The first region is used to grow a patterned gas-sensitive material layer in situ. S3. Place the exposed chip substrate in the precursor reaction solution to complete the in-situ patterned growth of the metal oxide-based gas-sensitive material to form a gas-sensitive material layer. S4. Remove the mask template, modify the surface of the gas-sensitive material layer with noble metal to form a noble metal structure layer, and anneal to obtain the wafer-level hydrogen sensor.
8. The preparation method according to claim 7, characterized in that, The chip substrate mentioned in step S1 is formed by spin-coating photoresist onto a substrate material, forming a photolithographic pattern on the substrate material through at least exposure, development, and removal of residual photoresist, and then fabricating an electrode array to obtain the chip substrate.
9. The preparation method according to claim 8, characterized in that, The substrate material is any one of silicon, silicon containing silicon dioxide, silicon nitride, gallium nitride, metal oxide ceramics, and polyimide.
10. The application of the high-throughput wafer-level hydrogen sensor according to any one of claims 1-6 in multi-component gas sensing.
